A review and outlook on expression of animal proteins in plants - Tusé, Daniel; McNulty, Matthew; McDonald, Karen A.; Buchman, Leah W. (Frontiers in Plant Science, 2024)
This review delves into the multifaceted technologies, benefits and considerations surrounding the expression of animal proteins in plants, emphasizing its potential role in advancing global nutrition, enhancing sustainability, while being mindful of the safety considerations. As the world's population continues to grow and is projected to reach 9 billion people by 2050, there is a growing need for alternative protein sources that can meet nutritional demands while minimizing environmental impact. Plant expression of animal proteins is a cutting-edge biotechnology approach that allows crops to produce proteins traditionally derived from animals, offering a sustainable and resource-efficient manner of producing these proteins that diversifies protein production and increases food security. In the United States, it will be important for there to be clear guidance in order for these technologies to reach consumers. As consumer demand for sustainable and alternative food sources rise, biotechnologies can offer economic opportunities, making this emerging technology a key player in the market landscape.